Financial Stress, Social Impacts, and Psychological Outcomes of Online Borrowing - Nurwulan Kusuma Devi; Suyanto; Haspul Naser (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid growth of online lending has improved financial access but has raised concerns about financial stress, social pressure, and psychological consequences among borrowers. This study addresses this gap by examining the borrower-centered impacts of online borrowing, which remain underexplored in prior research. The objective of this study was to analyze how financial stress and social impacts contribute to psychological outcomes. A qualitative approach was employed, using in-depth interviews with borrowers and industry practitioners, supported by document analysis. Data from 77 participants were analyzed using thematic analysis methods. The findings show that high interest rates and repayment obligations generate financial stress, disrupt social relationships, and lead to anxiety and reduced well-being. These results highlight the interconnected nature of the financial, social, and psychological challenges of online borrowing. This study offers practical implications for policymakers and lending platforms to develop more responsible and sustainable lending practices that better protect borrowers, particularly through stronger regulatory oversight, improved transparency in loan terms, and stricter controls on interest rate structures and collection practices. In addition, financial literacy programs and borrower education initiatives should be strengthened to help individuals make more informed borrowing decisions and manage repayment risks more effectively.